United Nations Commission on International Trade Law (UNCITRAL) Yearbook 2009 - United Nations (United Nations, 2013)
The United Nations Commission on International Trade Law (UNCITRAL) is the core legal body of the United Nations system in the field of international trade law. It specializes in the modernization and harmonization of rules on international business. The Commission is composed of sixty Member States elected by the General Assembly. This Yearbook reproduces the substantive documents prepared each year for the Commission and its working groups. It also includes the annual Report of the Commission, meeting records, General Assembly resolutions and Sixth Committee reports related to UNCITRAL’s work, as well as a bibliography of recent scholarly writings examining the legal texts prepared by UNCITRAL.